2004
DOI: 10.3354/dao062075
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific polymerase chain reaction primer sets for the diagnosis of Tenacibaculum maritimum infection

Abstract: In this study the specificity and sensitivity of 2 primer pairs, MAR1-MAR2 and Mar1-Mar2, for the detection of Tenacibaculum maritimum were evaluated in parallel using 79 T. maritimum strains isolated from different fish species, as well as 53 representatives of related and unrelated bacterial species. Both primer pairs were species-specific for T. maritimum, since no amplification products were obtained from chromosomal DNA of the non-T. maritimum bacteria tested. However, whereas MAR1-MAR2 identified all the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 23 publications
4
34
0
7
Order By: Relevance
“…Recent research comparing the specificity and sensitivity of these 2 primer pairs demonstrated that the Toyama PCR procedure is the most adequate for an accurate detection of Tenacibaculum maritimum in diagnostic pathology, as well as in epidemiological studies of marine tenacibaculosis (Avendaño-Herrera et al 2004c). Although this method proved useful in detecting acute T. maritimum infections in fish, the level of sensitivity was not sufficient to detect the pathogen when present in very low number in asymtomatic or carrier fish.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research comparing the specificity and sensitivity of these 2 primer pairs demonstrated that the Toyama PCR procedure is the most adequate for an accurate detection of Tenacibaculum maritimum in diagnostic pathology, as well as in epidemiological studies of marine tenacibaculosis (Avendaño-Herrera et al 2004c). Although this method proved useful in detecting acute T. maritimum infections in fish, the level of sensitivity was not sufficient to detect the pathogen when present in very low number in asymtomatic or carrier fish.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Then, Bader & Shotts (1998) also selected a pair of T. maritimum species-specific PCR primers Mar1 (5´-TGTAGCTTGCTACAGATGA-3´) and Mar2 (5´-AAATACCTACTCGTAGGTACG-3´), positions 77 to 98 and 1060 to 1081, respectively, from unique sequence stretches within this gene, delimiting a 400 bp DNA fragment. Unfortunately, the authors only tested these primers with pure cultures, and not with infected fish tissues.Recent research comparing the specificity and sensitivity of these 2 primer pairs demonstrated that the Toyama PCR procedure is the most adequate for an accurate detection of Tenacibaculum maritimum in diagnostic pathology, as well as in epidemiological studies of marine tenacibaculosis (Avendaño-Herrera et al 2004c). Although this method proved useful in detecting acute T. maritimum infections in fish, the level of sensitivity was not sufficient to detect the pathogen when present in very low number in asymtomatic or carrier fish.…”
mentioning
confidence: 99%
“…The detection limits of each primer set (cpn60F-cpn60R, sodAF-sodAR, cae1-caeVQ2 and PX1-PXVQ2) were evaluated in sensitivity assays using pure or mixed cultures as described by Avendaño-Herrera et al (2004). Separate bacterial suspensions of the 5 Streptococcus phocae strains were prepared to contain 10 9 cells ml -1 (McFarland Scale 4) and were 10-fold diluted in 0.85% sterile saline solution from 10 8 to 10 cells ml -1…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the data can easily be stored in databases, compared across experiments, and progressively enriched by the addition of new isolates. The generality of MLSA also makes it complementary to more rapid and less expensive detection methods, such as PCR or immunohistochemical assays already proposed for T. maritimum (33)(34)(35)(36) and T. soleae (37). To illustrate the applicability of our approach at the genus level, we include in this report the results of MLSA on a selection of isolates responsible for recent tenacibaculosis outbreaks in Norwegian salmon farms (38) and in Italian sea bass and sea bream farms.…”
mentioning
confidence: 99%